2022
DOI: 10.1002/joc.7898
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Weather Research and Forecasting model in simulating climate over northern Asia

Abstract: High-resolution simulation is important for understanding climate change and its impact over regions with complex terrain. Northern Asia (NA) is such a region and sensitive to global warming. However, the performance of the regional model over NA is still unclear. In this study, we conducted a twodecade-long high-resolution (25 km) simulation over NA using the Weather Research and Forecasting (WRF) model forced by the ERA-Interim reanalysis and then evaluated the performance of WRF against the observations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 77 publications
0
0
0
Order By: Relevance
“…On the other hand, high‐resolution regional climate models (RCMs) can better resolve the thermodynamic‐dynamical state of the atmosphere forced by mesoscale factors such as topography, improving the simulation of moisture transport and precipitation over complex regions of NWC (X. Yang et al., 2023; Yu et al., 2015). RCMs also show strength in reflecting the interactions between regional Earth system components associated with precipitation dynamics (Bai et al., 2022; Tang et al., 2019). Consequently, the coupling of RCMs and GCMs (RCM‐GCM) has been widely used in recent years to study the characteristics of regional precipitation variability and future climate change projections (X. Yang et al., 2023; Yao et al., 2019; H. Zhang & Gao, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, high‐resolution regional climate models (RCMs) can better resolve the thermodynamic‐dynamical state of the atmosphere forced by mesoscale factors such as topography, improving the simulation of moisture transport and precipitation over complex regions of NWC (X. Yang et al., 2023; Yu et al., 2015). RCMs also show strength in reflecting the interactions between regional Earth system components associated with precipitation dynamics (Bai et al., 2022; Tang et al., 2019). Consequently, the coupling of RCMs and GCMs (RCM‐GCM) has been widely used in recent years to study the characteristics of regional precipitation variability and future climate change projections (X. Yang et al., 2023; Yao et al., 2019; H. Zhang & Gao, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Current work on the PRR through RCM‐GCM has mostly focused on the Tibetan Plateau region (N. Jiang et al., 2022; H. Zhang & Gao, 2021). Existing studies showed that the RCM‐GCM can significantly improve performance of regional climate and produce more reliable future climate change projections (Bai et al., 2022; Tang et al., 2019; H. Zhang & Gao, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations